Cutaneous Manifestations as a Clinical Screening Index for Diabetic Microvascular Involvement: A Pilot Cross-Sectional Study - Laura Palacios-Abril; Aroa Tardáguila-García; Francisco Javier Álvaro-Afonso; Sol Tejeda-Ramírez; Yolanda García-Álvarez; José Luis Lázaro-Martínez (Diabetology, 2026)
Background and objectives: Diabetic microangiopathy is a frequent complication of diabetes mellitus, and its early identification remains challenging, particularly in resource-limited settings. This study aimed to develop a simple clinical scoring system based on cutaneous manifestations to estimate the risk of microangiopathy. Methods: An observational cross-sectional pilot study was conducted in 30 adults with diabetes mellitus attending a specialized diabetic foot unit. Lower-limb cutaneous manifestations (xerosis, absence of hair, hyperpigmentation, nail-plate thickening, skin atrophy and hypertrophy) were assessed during physical examination. Cutaneous findings significantly associated with clinically established microangiopathy were incorporated into a preliminary clinical screening index. Its discriminative ability was evaluated using receiver operating characteristic (ROC) analysis. As a secondary exploratory analysis, the relationship between the index and transcutaneous oxygen pressure (TcPO2) was investigated. Results: Five cutaneous manifestations were included in the final clinical screening index. The index demonstrated excellent discriminative ability for identifying clinically established microangiopathy (AUC = 0.95; 95% CI: 0.88–1.00). A cut-off value of ≥4 points yielded a sensitivity of 76.2% and a specificity of 100%. Higher index scores showed a trend towards lower TcPO2 values and a greater frequency of reduced tissue oxygenation, although these exploratory associations were not statistically significant. Conclusions: The proposed score shows promising discriminative performance. Although physiological associations were not statistically significant, observed trends support its potential clinical relevance. Further validation in larger cohorts is required.